2011
DOI: 10.1073/pnas.1100548108
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of CA3 hippocampal network activity by activation of group II metabotropic glutamate receptors

Abstract: Impaired function or expression of group II metabotropic glutamate receptors (mGluRIIs) is observed in brain disorders such as schizophrenia. This class of receptor is thought to modulate activity of neuronal circuits primarily by inhibiting neurotransmitter release. Here, we characterize a postsynaptic excitatory response mediated by somato-dendritic mGluRIIs in hippocampal CA3 pyramidal cells and in stratum oriens interneurons. The specific mGluRII agonists DCG-IV or LCCG-1 induced an inward current blocked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 38 publications
6
33
0
Order By: Relevance
“…This effect is likely due to direct actions of the group II agonist on the postsynaptic neuron, as the experiments were performed in the presence of TTX. Although the exact mechanism by which mGlu 3 , a G i/o coupled receptor, induces intracellular Ca 2+ increases is unknown, similar effects of group II mGlu receptor agonists on intracellular Ca 2+ are observed in hippocampal CA3 pyramidal cell and interneuron populations, and these responses are thought to be mediated by activation of mGlu 3 (29). In addition, there are examples of other G i/o coupled receptors inducing intracellular Ca 2+ elevations (30).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is likely due to direct actions of the group II agonist on the postsynaptic neuron, as the experiments were performed in the presence of TTX. Although the exact mechanism by which mGlu 3 , a G i/o coupled receptor, induces intracellular Ca 2+ increases is unknown, similar effects of group II mGlu receptor agonists on intracellular Ca 2+ are observed in hippocampal CA3 pyramidal cell and interneuron populations, and these responses are thought to be mediated by activation of mGlu 3 (29). In addition, there are examples of other G i/o coupled receptors inducing intracellular Ca 2+ elevations (30).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of presynaptic GPCRs provides a powerful means to modulate information flow (20,21). It has historically been difficult to study neuromodulatory influences on long-range synaptic connectivity, and, to date, only a few studies have investigated GPCR modulation of presynaptic release from ChR2-expressing terminals (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of presynaptic G protein-coupled receptors (GPCRs) powerfully regulates information flow in neural circuits by modulating presynaptic release probability (20,21). Having established the functional network organization of the corticoraphe circuit, we next examined its potential regulation by neuromodulation, specifically asking whether PFC synapses onto 5-HT and GABA neurons were differentially modulated by GPCR activation.…”
Section: Feed-forward Inhibition Of Local Drn Gaba Interneurons By Opmentioning
confidence: 99%
“…The loci meeting genome-wide significance in the largest genome-wide association study of schizophrenia ever conducted [8] include genes coding proteins shown to directly affect neuronal oscillations, such as MGluR3 ( δ , θ , and β ) [56, 57], GluR1 ( δ – γ interactions) [58], HCN ( θ and α ) [41, 42, 59], nAchR ( θ ) [60], T-type calcium channels ( δ ) [44], and Nr2Ar ( γ ) [61]. Further genome-wide associations concern genes that may be indirectly involved in rhythms, expressed in GABAergic interneurons, or regulate synaptic transmission or neurodevelopment [8, 9].…”
Section: Cellular Molecular and Circuit Level Changes Alter Rhythmsmentioning
confidence: 99%